Comparative Aspects of Administrative Contracts and Civil-Private Contracts - Imami, Ahmet; Alishani-Sopi, Detrina (PRAWO i WIĘŹ, 2025)
The purpose of this article is to deal with the comparative aspects between administrative contracts and civil-private contracts, analyzing the differences and similarities between them. This analysis in the comparative aspects of these two types of contracts will serve in relation to the definitions and characteristics, the entities that bind these contracts, the legal status of the contracting parties, the legal infrastructure by which these two types of contracts are regulated, the dispute resolution procedure between the contracting parties (in case of any eventual dispute), the way of changing or canceling them, etc. In addition to the differences between administrative contracts and civil-private ones, during the treatment of this paper, the differences between administrative contracts and other forms of administrative activity and the differences between civil-private contracts and contracts of other branches will be elaborated.